Land, territory and commons: voices and visions from the struggles. Issue 7 (2nd October 2020) - Ferrando, Tomaso; Vispo, Isabel Álvarez; Anderson, Molly; Dowllar, Sophie; Friedmann, Harriet; Gonzalez, Antonio; Maracle, Chandra; McKeon, Nora
ABSTRACT: All over the world, financial capitalism and extractivism are appropriating land as if it was nothing more than a commodity, a mere 'factor' of production that can be exploited to generate financial returns. Movements and activists are organizing, resisting, protecting and promoting life-giving visions against this continuous enclosure of living beings and paces: they use their bodies, laws, educational projects, histories and visions to regain control over territory as a political space, self-determine and create solidarities. In the act resistance, they are the target of moral, physical and legal violence. They and their ideas are criminalized, disciplined, punished and in some cases exterminated. In this contribution, activists from the Basque Country, Guatemala, Kenya and the Six Nations and a group of academics get together to learn from each other, support the ongoing search for common vocabularies and identify possible milestones of a coordinated and international strategy for a life-enhancing future.